(3LQGFe GHGOI GdLfS GdHTQi ai efXhQ GdbGfhf GdOhdi hGdbGfhf GdLfGFi (B/ s - (3eMeO GHQGgje NdjaI GdQejMis; (3e(BH(3eCehf eMeO SdGeI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jJeKd GdgOa GdGSGSi ef OQGSI LQGFe GHGOI GdLfS GdHTQi ai efXhQ GdbGfhf GdOhdi h GdbGfhf GdLfGFi Gf fdbi LGfHG ef GdVhA Ydi GgejI GdGdJRGe HGJaGbjI QheG GdJi JYfi HeMGceI eLQei GdMQH GdPjf jbJQahf LQGFe GdGHGOI GdLeGYjI ddHTQ (B: (3fXQG dGf LQjeI GHGOI GdLfS GdHTQi LQjeI TfYGA h GKGQgG hNjeI Ydi GdeLJeY GdhWfi h GdeLJeY GdOhdi HTcd YGe (B: (3hGdOhd GdYQHjI HTcd NGUs
(3jTJed Ydi edGMb(B: (3UaMI (B165-225s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B227-232s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GHGOI GdLfS GdHTQis; (3GdJTQjY GdLfGFi GdGSdGeis; (3GdLQGFe GdOhdjIs; (3GdgOfI GdEdgjIs; (3ejKGb HQjGf cjdhNs; (3GYeGd GdEQgGHs; (3GdGSJFUGds; (3GdSdGe GdEdgj s; (3eHOC GdJcGeds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs